Penyuluhan Manajemen Pemasaran Berbasis Online (E-Commerce) Dalam Peningkatan Kapasitas Berbagai Produk Melalui E-Marketplace di Kota Jambi - Pratiwi, Heni; Hutabarat, Zuhri Saputra; Parkhurst, Helen; Afrila, Diliza; Aprizal, Yusuf Zaini; Pratama, Aditya; Roihan, Muhammad (Yayasan Cita Cendikiawan Al Kharizmi, 2024)
With the rapid development of information technology, many changes have occurred in the way of human life. This requires humans to always adjust their lifestyles to technological developments. All buying and selling activities or transactions carried out using electronic media (internet) in the term e-commerce. The usefulness of information technology is to improve organizational performance, increase the effectiveness and efficiency of time, energy, costs, increase production, promotion and sales. Marketing carried out using internet technology is known as e-marketing. One of the leading products of MSMEs in Jambi Province is Batik. So far, the batik marketing strategy that relies heavily on capital accumulation, protection, and high technology has caused polarization and dualism in the distribution process of Batik in Jambi Province. Therefore, it is necessary to strengthen the marketing capacity of the creative batik industry through e-marketplaces by using them as a forum for interactive electronic business communities that provide a market where batik can be introduced nationally. E-Marketplace is an internet-based online media (web based) where business activities and transactions between buyers and sellers are carried out. Buyers can search for as many suppliers as possible with the desired criteria, so that they get according to market prices. Meanwhile, suppliers/sellers can find out companies that need their products/services. The approach used in this study is the System Development Life Cycle (SDLC) method, a systematic approach to designing/planning, designing, implementing and evaluating a system related to e-market place.